Knowledge, attitudes and practices regarding TB infection control among health science students in a TB-endemic setting - van der Westhuizen, Helene-Mari; Kotze, Koot; Narotam, Heena; von Delft, Arne; Willems, Bart; Dramowski, Angela (International Journal of Infection Control, 2015)
Medical and physiotherapy students in tuberculosis (TB)-endemic settings are at high risk of developing occupational TB. Didactic lectures are the traditional method for delivering education on the topic of TB infection control (TB-IC) to undergraduate health science students. The aim of this study was toevaluate the impact of a novel educational package for teaching TB-IC to undergraduate health science students in a TB-endemic setting. Undergraduate medical and physiotherapy students at Stellenbosch University, South Africa (n = 326) participated in a cross-sectional survey documenting TB-IC knowledge, attitudes and TB-IC practices at the training institution. A self-administered questionnaire was completed before and after a novel educational intervention which utilized the health belief model (and included personal testimonials from healthcare workers and an IC expert who had survived occupational TB). Students perceived themselves to be at high risk of occupational TB, but underestimated drug-resistant TB mortality. Pre-intervention knowledge of TB-IC measures was poor, but improved post-intervention (58% vs 78% [p < 0.001]). Senior students had better pre-intervention knowledge of N95 respirator use. Negative attitudes and TB-IC practices of senior staff at the training institution reportedly influenced those of students. TB-IC measures (natural and mechanical ventilation; airborne precaution signage; patient isolation) were reportedly poorly implemented. Access to personal protective equipment was problematic with 49% (87/177) of senior students stating that N95 respirators were never available. In conclusion, students lack knowledge of TB-IC measures and report poor implementation of TB-IC measures at their training institution. A novel structured educational intervention increased students’ knowledge of TB-IC measures and heightened awareness of occupational TB risk.